SMC-COM STOCK PRICE ANALYSIS BEFORE AND DURING THE COVID-19 PANDEMIC - Hermawan, Yana; Nurrahmawati, An; Atmalistya, Avi (Faculty of Administrative Science, Universitas Brawijaya, 2025)
Main Purpose – Comparative analysis of the impact of fundamentals and macroeconomics on SMC-Com stock price movements before and during Covid19 pandemic.Method – By using the purposive sampling approach, samples were chosen. Data on SMC-Com's fundamental and macroeconomic variables were tested using multiple linear regression.Main Findings – Under various circumstances, each ratio has a varying impact on the SMC-Com index. Consequently, investors should concentrate on the ratios that affect stock prices while considering the situation for a more effective study.Theory and Practical Implications – Fundamental factors, macroeconomics, and the prevailing situation should be analyzed by investors simultaneously.Novelty – Comparative testing in the context before and during the Covid-19 pandemic on the share prices of small and medium-sized entities indexed on SMC-Com.